Heterosynaptic Plasticity and the Experience-Dependent Refinement of Developing Neuronal Circuits - Jenks, Kyle R.; Tsimring, Katya; Ip, Jacque Pak Kan; Zepeda, Jose C.; Sur, Mriganka (Frontiers in Neural Circuits, 2021)
Neurons remodel the structure and strength of their synapses during critical periods of development in order to optimize sensory processing. Many of these developmental changes are thought to occur through synapse specific homosynaptic forms of experience-dependent plasticity, where synapses that are directly affected by changes in activity are the ones that undergo modifications in strength. However, homosynaptic plasticity can also induce or contribute to the plasticity of neighboring synapses through heterosynaptic mechanisms. Decades of research in vitro have uncovered a host of molecular mechanisms for forms of heterosynaptic plasticity that underlie local compensation for homosynaptic plasticity, facilitation of further bouts of plasticity in nearby synapses, and cooperative induction of plasticity by neighboring synapses acting in concert. These discoveries greatly benefited from new tools and technologies that permitted single synapse imaging and manipulation of structure, function, and protein dynamics in living neurons. With the recent advent and application of similar tools for in vivo research, it is now feasible to explore how heterosynaptic mechanisms contribute to critical periods and developmental plasticity. In this review, we will first define the forms heterosynaptic plasticity can take and describe our current understanding of their molecular mechanisms. Then, we will outline how heterosynaptic plasticity may lead to meaningful refinement of sensory driven responses and observations that suggest such mechanisms are indeed at work in vivo. We will detail the molecular overlap between heterosynaptic plasticity and a well described form of critical period plasticity that occurs during the development of the binocular visual cortex; ocular dominance plasticity. Finally, we will discuss how heterosynaptic plasticity could explain conflicting and contentious findings from studies of ocular dominance plasticity, and suggest potential avenues of future research.